Poesia – pensamiento / palabra – cosa acerca del texto “la esencia del habla” de Martin Heidegger - González Ramírez, Gloria Inés (Nómadas. Critical Journal of Social and Juridical Sciences, 2006)
This work presents the philosophical analysis of the three lectures of Mr. Heidegger that make up his topic “The essence of speech”. It becomes the possibility of making an experience out of speech, in the context, the field of speech not about or in reference to speech. This document shares all previous experience by following Jaime Hoyos, SJ, in several seminars about the author. In the first lecture Philology is chosen as the path to access the region of speech; we find that words open, they break and thus make possible for us to see-listen what is at the bottom. Words are necessary in order for things to exist. But the technical analysis is not enough. Things do not just exist. By existing, they are immersed in the name of their name. Neither is it enough to recognize man as custodian of the image of the being and the word. Therefore, in the second lecture it is introduced a path and a way of walking along that path not from the scientific method but from the philosophical thought. In the vicinity speech-poetry it is the poets who make the experience when they reject the arrogance of owner and provider of the word; when they give themselves unrestrictedly to sing songs, sayings of their conscience that summon them. It is wondering on the regions of speech when the path becomes the inaugural word of speech. The third lecture takes as starting point the fact of having placed us in the path so that we can reach what our essence rightly demands. The vicinity Poetry-Thought summons the essence of speech that is the speech of essence. The proximity, the closeness of all instances of the universe that must be said in order to appear in donation and discovering so that it is woven the universal fabric of the relationships among all regions of the world. The “being” happens where the word breaks.